Medicago sativa and Medicago truncatula Show Contrasting Root Metabolic Responses to Drought - Echeverria, Andres; Larrainzar, Estíbaliz; Li, Weiqiang; Watanabe, Yasuko; Sato, Muneo; Tran, Cuong Duy; Moler, Jose A.; Hirai, Masami Yokota; Sawada, Yuji; Tran, Lam-Son Phan; Gonzalez, Esther M. (Frontiers in Plant Science, 2021)
Drought is an environmental stressor that affects crop yield worldwide. Understanding plant physiological responses to stress conditions is needed to secure food in future climate conditions. In this study, we applied a combination of plant physiology and metabolomic techniques to understand plant responses to progressive water deficit focusing on the root system. We chose two legume plants with contrasting tolerance to drought, the widely cultivated alfalfa (Medicago sativa, Ms) and the model legume Medicago truncatula (Mt) for comparative analysis. Ms taproot (tapR) and Mt fibrous root (fibR) biomass increased during drought, while a progressive decline in water content was observed in both species. Metabolomic analysis allowed the identification of key metabolites in the different tissues tested. Under drought, carbohydrates, abscisic acid, and proline predominantly accumulated in leaves and tapRs, whereas flavonoids increased in fibRs in both species. Raffinose-family related metabolites accumulated during drought. Along with an accumulation of root sucrose in plants subjected to drought, both species showed a decrease in sucrose synthase (SUS) activity related to a reduction in the transcript level of SUS1, the main SUS gene. This study highlights the relevance of root carbon metabolism during drought conditions and provides evidence on the specific accumulation of metabolites throughout the root system.